The Effect of Variations in Electrolyte Temperature and Current Strength on the Synthesis of Manganese Dioxide from Manganese Sulfate Precursors by Electrolysis Method - Rizta Febian Adi Endani (National Research and Innovation Agency (BRIN), 2021)
The development of science and technology today in the field of electronics, especially energy storage increases the demand for the use of lithium secondary batteries. The development of lithium batteries is focused on energy storage capacity by using manganese dioxide (MnO2) as a lithium battery cathode material. Manganese dioxide was chosen as the cathode material for lithium batteries because it has a high storage capacity of about 615 mAh/g compared to other materials such as graphite which has a storage capacity of 372 mAh/g and has a low toxicity of 0.14 mg/kg. MnO2 was synthesized by electrolysis method from manganese sulfate (MnSO4) precursor which was obtained from Trenggalek manganese ore leaching process. The electrolysis process was carried out for 5 hours using variations in electrolyte temperature of 30, 40, 50 and 60oC as well as variations in current strength of 2, 3, 4 and 5 A to determine the effect of electrolyte temperature and current strength on mass gain, structural polymorphy and morphology of MnO2 formed. The highest mass gain was obtained at the use of an electrolyte temperature of 60oC and a current of 5 A, which was 11.4 grams with the polymorphy structure of the MnO2 compound formed was α-MnO2 polymorphy. SEM image shows that the MnO2 particles have a spiny round shape and tend to agglomerate with particle diameter values ranging from 50 nm - 170 nm. Keywords: Electrolysis, MnO2, MnSO4, Electrolyte temperature, Current strength